The Implementation of Qānūn of Jināyāt in Aceh: A Legal Point of View - Fauzah Nur Aksa; Saifullah, T; Farabi, Al (Fakultas Syariah, Universitas Islam Negeri Raden Mas Said Surakarta, 2023)
Aceh is the only region in Indonesia granted special rights to implement Islamic law within its territory, as stipulated in Law No. 44 of 1999 regarding the administration of special autonomy in the Aceh Special Region. This uniqueness can be seen as a political solution to the long-standing conflict in Aceh. Several institutions serving as enforcers of Islamic law were established to support the implementation of local regulations on Islamic law, including the Sharia Court, the Sharia Office, and the Wilayatul Hisbah. Additionally, the Aceh regional government collaborates with the police and the prosecutor's office, where they act as investigators, interrogators, and public prosecutors in the implementation of Islamic law. This research examines the implementation of the qānūn of jināyāt in Aceh. The research findings indicate that the implementation of Islamic law in Aceh faces several challenges. Firstly, the Wilayatul Hisbah faces issues related to their authority, as according to Sharia rules, their role is limited to supervision, while investigation falls under the jurisdiction of the police. In practice, the police often disregard Islamic law in Aceh, mainly due to several provisions conflicting with national laws. Consequently, many cases of Sharia violations end with reconciliation processes within the police and do not proceed to court prosecutions. Secondly, the execution process is often lengthy, and in many cases, execution is neglected. The principles of equality before the law and legal certainty have not yet become primary principles in the application of Islamic law in Aceh.